A Protocol For A Retrospective Cohort Analytic Study To Determine The Relative Risk Of Abnormal Reproductive Outcomes For Medical Laboratory Technologists Compared To Physiotherapists - Johnston, Warwick Neil (My University, 1981)
A retrospective cohort analytic study will be conducted to compare the incidence of abnormal reproductive outcomes of members of the Canadian Society of Laboratory Technologists with that of members of the Canadian Physiotherapy Association in order to identify exposures which may pose a threat to the reproductive process.
Members of each of the organizations will be mailed a questionnaire requesting demographic and health information. A second questionnaire requesting detailed information about reproductive outcomes will be sent to those subjects who have experienced pregnancies in the previous five years. Additional mailings by conventional mail and special delivery wil be used to increase the response rate. Subjects who have given birth to stillborn children or children with congenital abnormalities and a random sample of those who have had miscarriages will be asked to provide written consent for their physician to be contacted to provide confirmatory information from their medical record.
The analyses will compare rates of abnormal reproductive outcomes in total and by specific type between laboratory technologists and physiotherapists controlling for age, parity, smoking status, infection, X-ray, drug and alcohol exposure during pregnancy.
Keywords: Medical Sciences; Medical Sciences